PERAN SERTA MASYARAKAT DALAM MEMPERTAHANKAN KAWASAN HUTAN LARANGAN ADAT IMBO PUTUI - Deddy Samuel; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The Imbo Putui Prohibition Forest is a traditional forest located in Petapahan Village. The existence of the community has a role in the management and preservation of the forest environment. Where the existence of the forest is closely related to the living things in it. The purpose of the study was to determine the community's role in efforts to maintain the Imbo Putui Prohibition Forest Petapahan Village Tapung District Kampar Regency Riau Province and to know the factors of the community's role in maintaining the Imbo Putui Prohibition Customary Forest Petapahan Village Tapung District Kampar Regency Riau Province. This study uses a random sampling method. Determination of the number of respondents in this study used the Slovin formula with a level of 10% so as to get 96 respondents. Data collection is done by interview, observation and literature study. Community participation is obtained through community leaders, customary law and state law. The community factor in maintaining the Imbo Putui Prohibited Forest area is inheritance from the ancestors and the community is aware of the existence of the Imbo Putui Prohibited Customary Forest as a habitat for flora and fauna.Keywords : Customary forest prohibition, forest, the role of society.